-8x+8+10x=2x+1
-8x+10x-2x=1-8
(-8+10-2)x=-7
0x=-7
No solution as 0x=0 with all values of x
2007-03-12 20:24:53
·
answer #1
·
answered by beuuu 2
·
0⤊
0⤋
in the starting up upload the like words by ability of transferring the 10x next to the -8x. Then simplify.(The transferring of the 10x is termed the "commutative resources.") -8x+8+10x = 2x +a million -8x+10x+8=2x+a million 2x + 8 = 2x + a million 2d of all, get the variables all to one area. To get each of the variables to one area, subtract 2x from both area: 2x + 8 = 2x + a million 2x - 2x +8 = 2x - 2x +a million you're left with 8=a million. the answer? No answer.
2016-12-01 22:18:51
·
answer #2
·
answered by ? 4
·
0⤊
0⤋
-8x + 8 + 10x = 2x +1
(8x +-8x) + 10x = (8x + 2x) + 1
8 + 10x = 10x + 1
(8 - 1) + 10x = 10x + (1 - 1)
7 + 10x = 10x
7 + (10x / 10x) = (10x / 10x)
7=x
2007-03-12 20:14:05
·
answer #3
·
answered by ? 4
·
0⤊
0⤋
–8x + 8 + 10x = 2x + 1
+ 8 + 2x = 2x + 1
+ 2x = 2x + 1 - 8
+ 2x = 2x - 7
+ 2x - 2x = - 7
0 = -7
But
0 ╪ -7
It looks like the equation is not typed out right.
2007-03-12 20:08:26
·
answer #4
·
answered by Brenmore 5
·
1⤊
1⤋
Gather all the "x" terms on one side and all the numbers on the other
-8x + 10x - 2x = -8 +1
0x = -7 Your original equation is not possible, or not written out correctly.
2007-03-12 20:07:26
·
answer #5
·
answered by Anonymous
·
1⤊
1⤋
hey this eqn. is a false eqn.
u can know this by puttin any value of x
lets say x=1
-8x+8+10x=2x+1
-8+8+10=2+1
10=! 3
2007-03-12 20:30:30
·
answer #6
·
answered by PUNJABI ROCKS 2
·
0⤊
1⤋
–8x + 8 + 10x = 2x + 1
-8x+10x-2x = -8+1
-10x+10x = -7
0x=-7
Therefore, x is infinite.
2007-03-12 20:47:19
·
answer #7
·
answered by St Harpy 6
·
0⤊
1⤋
no answer
rearrange all the variables on one side and all real numbers on the other.
So...
-8x+10x-2x=1-8
0x=-7
x=-7/0 or undefined
2007-03-12 22:02:47
·
answer #8
·
answered by al 3
·
0⤊
0⤋
- 8x + 8 + 10x = 2x + 17
2x + 8 = 2x + 17
2x + 8 - 2x = 2x + 17 - 2x
8 = 17
No solution. The coefficient and variable cancell.
- - - - - - - - -s-
2007-03-12 21:34:41
·
answer #9
·
answered by SAMUEL D 7
·
0⤊
0⤋
You can't.
-8x + 8 + 10x = 2x + 1
2x + 8 = 2x +1
That's a false statement.
2007-03-12 20:06:54
·
answer #10
·
answered by questionallthings 2
·
1⤊
1⤋